Prominent oncocytic metaplasia in pleomorphic adenoma: A potential diagnostic pitfall. Issue 8 (25th April 2020) - Ito, Hiroko; Ishida, Mitsuaki; Miyasaka, Chika; Okano, Kimiaki; Sandoh, Kaori; Fujisawa, Takuo; Iwai, Hiroshi; Tsuta, Koji
Abstract: Pleomorphic adenoma (PA) is the most common salivary gland tumor. The cytological features of PA are well recognized, and its diagnosis is straightforward in most cases. Some metaplastic changes in PA are well known; however, occurrence of oncocytic metaplasia in PA is very rare. In this report, we describe the first cytological case of prominent oncocytic metaplasia in PA identified based on immunocytochemical analysis. We report the case of a 62‐year‐old Japanese female who presented with swelling of the left neck region. A fine‐needle aspiration cytologic examination was performed followed by surgical resection. The Papanicolaou smear revealed the presence of discohesive neoplastic cells in a myxoid background. These neoplastic cells had a relatively rich, granular cytoplasm, and round nuclei with moderate pleomorphism. Initial cytodiagnosis revealed carcinoma ex PA (CXPA). Immunocytochemical analysis showed that abundant mitochondria were present in the cytoplasm of these neoplastic cells. Histopathological examination of the resected tumor demonstrated proliferation of oncocytic neoplastic cells within a myxoid material and the presence of conventional PA components. A final diagnosis of prominent oncocytic metaplasia in PA was made. Oncocytic metaplasia showed nuclear atypia and pleomorphism; therefore, CXPA, which presents with severe nuclear atypia and necrotic background, must be differentiated from oncocytic metaplastic PA. Recognition of oncocytic metaplasia in PA is important for correct diagnosis.